MUSLIM CEO AND ISLAMIC SOCIAL REPORTING DISCLOSURE: EVIDENCE FROM INDONESIA - Dian Yuni Anggraeni; Rayna Kartika; Yuskar Yuskar (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2020)
Corporate social responsibility (CSR) has been attracting ever considerable attention from practice and academia, but the determinants of CSR remain unclear. The Islamic principles of vicegerency (khalifah) and brotherhood (ukhuwwah) is seen as closely connected to CSR, called Islamic Social Reporting (ISR). Thus, this study aims to examine the presence of Muslim CEO on ISR disclosure. Using regression analysis, this empirical study covers a sample of firms which are listed in the Jakarta Islamic Index (JII) for the year 2016-2018. The result reveals that Muslim CEO has a positive and significant relationship with ISR disclosure. It suggests that the attribute of board (CEO) has an importance role to enhance ISR engagement among corporation, especially a religion background of CEO as Islam emphasises the relationship between Allah and man and Allah and the environment or the nature.